Comparison of carotid plaque burden among healthy middle-aged men living in the US, Japan, and South Korea. (1st September 2018) - Vishnu, Abhishek; Choo, Jina; Kadota, Aya; Barinas-Mitchell, Emma J.M.; Fujiyoshi, Akira; Long, Dorothy Leann; Hisamatsu, Takashi; Ahuja, Vasudha; Nakamura, Yasuyuki; Evans, Rhobert W.; Miura, Katsuyuki; Masaki, Kamal H.; et al.
Abstract: Background: Carotid plaque has emerged as a marker of coronary heart disease (CHD) risk. Comparison of carotid plaque burden between different race/ethnic groups may provide a relative estimate of their future CHD risk. Methods: We conducted a population-based study among apparently healthy middle-aged men aged 40–49 years (ERA JUMP study (n = 924)) and recruited 310 Whites in Pittsburgh, US, 313 Japanese in Otsu, Japan, and 301 Koreans in Ansan, South Korea. The number of carotid plaque and CHD risk factors was assessed using a standardized protocol across all centers. The burden of carotid plaque was compared between race/ethnic groups after adjustment for age and BMI, and after multivariable adjustment for other CHD risk factors using marginalized zero-inflated Poisson regression models. Cross-sectional associations of risk factors with plaque were examined. Results: Whites (22.8%) had more than four-fold higher prevalence (p < 0.01) of carotid plaque than Japanese men (4.8%) while the prevalence among Koreans was 10.6%. These differences remained significant after adjustment for age, BMI as well as other risk factors – incidence density ratio (95% confidence interval) for plaque was 0.13 (0.07, 0.24) for Japanese and 0.32 (0.18, 0.58) for Koreans as compared to Whites. Age, hypertension and diabetes were the only risk factors significantly associated with presence of carotid plaque in the overall population. Conclusion: Whites have significantly higher carotid plaque burden than men in Japan and Korea. Lower carotid plaque burden among Japanese and Koreans is independent of traditional CVD risk factors. Highlights: White men in the US have four-fold higher carotid plaque than Japanese and twice as much as Koreans. These differences persist after accounting for lower BMI among east Asians in the study. Overall, age, hypertension and diabetes status are associated with higher carotid plaque burden.